Pengaruh Celebrity Endorser Tomorrow X Together dan Brand Image Terhadap Keputusan Pembelian Produk Sampo Kundal - Sari, Fifinnela Winie; Geofany, Sheren; H, Heriyanto (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The increasing consumption of foreign products by the public has prompted companies to intensify their promotional efforts through celebrity endorsers and brand image in order to boost product purchases. This research, conducted by the researcher, utilizes the variables of celebrity endorser and brand image to assess the significance of purchase decisions regarding Kundal shampoo products originating from South Korea. The research involved a purposive sample of 90 respondents who match with the criteria, including having purchased and used Kundal shampoo products and being familiar with Kundal shampoo through Tomorrow X Together. The researcher employed a casual approach with a survey method using an online distributed questionnaire. The SPP software was utilized to generate data ouput. The findings from this research reveal that there is no positive significance between the celebrity endorser Tomorrow X Together and purchase decisions. However, there is a positive significance between brand image and purchase decisions. Thus, H1 in this research can be considered rejected, while H2 is accepted.